Differential FVF Based Compact Rail-to-Rail Buffer Amplifier for LCD Column Drivers - (:unkn) unknown (IEEE COMPUTER SOC, 2018)
This paper presents an ultra-compact rail-to-rail buffer amplifier for large size liquid crystal display column drivers. The proposed circuit is mainly composed of a differential flipped voltage follower as the input stage and an inverter based output stage. It does not need an additional current comparator stage and because of this a very simple and compact circuit structure is obtained which uses only 10 MOS transistors. Supplied from a single 3.3V supply, the proposed high performance buffer amplifier is able to drive a 1 nF load within a 0.4 mu s settling time under a full voltage swing and it draws only 4.45 A quiescent current. All simulations are performed with HSpice using AMS 0.35 mu m triple-well CMOS technology parameters. The proposed circuit is compared to previously published circuits using a well-known Figure-of-Merit value and it is shown that it has outstanding performance parameters with the highest Figure-of-Merit value. Monte Carlo results are also performed to confirm the robustness of the compact amplifier topology.
Keywords: Buffer amplifier; liquid crystal display; column driver; rail-to-rail operation; flipped voltage follower; CLASS-B BUFFER; OUTPUT BUFFER; CMOS BUFFER